THE CONVERGENCE OF ART AND SCIENCES IN DIGITAL AGE: SOME PERSPECTIVES FROM NYAWA EXHIBITION IN MALAYSIA. - Baharuddin, Mohd Nasir; Salehuddin, Adam Mohd; Zaman, Faridah Qamaruz; Noor, Ahmad Shukri Muhammad (Proceeding of the International Conference on Arts and Humanities, 2019)
This article tries to introduce the idea of art and science into new contemporary aesthetics in the contexts of digital age in Malaysian art. This aesthetic field of investigation has led to a reassessment of representation based on Nature’s Yield and Wonders of Art (NYAWA) exhibition. The exhibition process will be structured by using ‘visual and discourse analysis’ methodology where the process of information and visual data will be shaped and investigates pertaining to the integration of art and science and how the exhibition materials and the language can be intersect. As a result, it tries to open a new gap of various disciplines in producing new ideas which enhance more dialogs and avenues between art and science as a creative convergence. Hopefully, this paper will try to operate an innovative and engaging manner, in order to support the development of new interpretive methodologies among scientists and artists to gives new ideas for future artistic creation. As a result, it can intrigue new directions for the visual arts industries. Indeed, search for balance to the convergence of science and art. Furthermore, this convergence can foster the interdisciplinary and collaborative work that is essential in building New Malaysian Contemporary Art.